Animal performance and sward characteristics of xaraés palisade grass pastures subjected to different grazing intensities, during rainy season - Carloto, Marciele Neves; Euclides, Valéria Pacheco Batista; Montagner, Denise Baptaglin; Lempp, Beatriz; Difante, Gelson dos Santos; de Paula, Cássia Cristina Lemes (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the nutritive value, sward structure, herbage intake and animal performance on xaraés palisade grass (Urochloa brizantha cv. Xaraés) pastures with 15, 30 and 45 cm sward heights, under continuous stocking, during rainy season. Monthly, the pastures were sampled for estimating the sward characteristics and the animals were weighted. Forage production decreased with the increase of grazing intensity; however, the 15-cm sward height pasture showed the greatest nutritive value. Dry matter intake was lower in the 15-cm pasture (1.89% live weight – LW) than in the 30 cm (2.26% LW) and 45 cm (2.34% LW) pastures. The average daily gain was similar among the different sward heights, with 730 g per steer average. The stocking rates were lower for the 45 cm (2.0 AU ha-1) and 30 cm (2.5 AU ha-1) pastures than for the 15 cm (3.5 AU ha-1) pasture. There was a greater gain per area for the 15 cm (678 kg ha-1) pasture than for the 45 cm (324 kg ha-1) pasture.